2017
DOI: 10.1099/jmm.0.000566
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high levels of resistance to linezolid and vancomycin in Staphylococcus aureus

Abstract: Both methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) are rapidly overcoming the current array of drugs. One hundred and fifty isolates from a hospital were studied for resistance towards linezolid and vancomycin. Fifty-four (36.0 %) isolates were MRSA. Both MRSA and MSSA showed high resistance towards linezolid when using the disc diffusion method, with the figures being 48.1 and 29.2 %, respectively. The figures for the E-test were 46.3 and 27.0 %, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 17 publications
4
28
1
1
Order By: Relevance
“…Also, the European mean proportion of linezolid resistance among MRSA blood isolates included in this study was found to be very 1ow [0.29% (95% CI 0.21-0.40%)], attesting to the overall susceptibility of MRSA isolates to linezolid in Europe. This is also similar to local studies in Germany and Spain (Sierra et al, 2013;Yayan et al, 2015), Russia (Gostev et al, 2015), China (Huang et al, 2019), and Latin America (Vega and Dowzicky, 2017), but remarkably lower compared to results from Pakistan (48.1%) (Azhar et al, 2017) and India (2.8-7.0%) (Kaur and Chate, 2015;Kumar, 2016). In comparison to other multi-country surveillance studies, such as ZAAPS and SENTRY, linezolid activity against VREF and MRSA remains similarly very high (>98%) in Europe (Mendes et al, 2016;Deshpande et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Also, the European mean proportion of linezolid resistance among MRSA blood isolates included in this study was found to be very 1ow [0.29% (95% CI 0.21-0.40%)], attesting to the overall susceptibility of MRSA isolates to linezolid in Europe. This is also similar to local studies in Germany and Spain (Sierra et al, 2013;Yayan et al, 2015), Russia (Gostev et al, 2015), China (Huang et al, 2019), and Latin America (Vega and Dowzicky, 2017), but remarkably lower compared to results from Pakistan (48.1%) (Azhar et al, 2017) and India (2.8-7.0%) (Kaur and Chate, 2015;Kumar, 2016). In comparison to other multi-country surveillance studies, such as ZAAPS and SENTRY, linezolid activity against VREF and MRSA remains similarly very high (>98%) in Europe (Mendes et al, 2016;Deshpande et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…15,25 In the current study, resistance to linezolid was reported as 37% in S. aureus isolates while in CoNS it was 90%. Previous study conducted in Pakistan reported cfr gene in 78% of linezolid resistant S. aureus isolates 24 which is higher than our results, although we observed high resistance of linezolid in CoNS. The increase in rate of resistance against linezolid is very alarming, particularly among CoNS which are developing resistance to other antibiotics as well.…”
Section: Discussioncontrasting
confidence: 97%
“…One study from Pakistan recorded high levels of vancomycin resistance in MRSA as 13% using E-test method. 24 Reason for increase in rate of resistance to vancomycin could be inadequate use of vancomycin and transfer of vancomycin resistance genes (vanA-C) from other vancomycin resistant organisms such as Enterococcus. Particularly our clinicians should be concerned about these reports on vancomycin resistance so that they can prescribe vancomycin accordingly to avoid therapeutic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also indicated that linezolid or tedizolid might not be the first-line choices of the antibiotics suitable for the antimicrobial treatment of E. faecalis infections in this hospital settings. Therefore, the resistance mechanism and risk factors of linezolid-resistant/intermediate E. faecalis infections deserve our attention and need to be further studied.Several previous reports have indicated the clonality characteristics of linezolid resistance in Staphylococci and E. faecalis(21,22). ST16 is the predominant STs of linezolidresistant/intermediate E. faecalis clinical isolates in this study.…”
supporting
confidence: 66%